Proposing a New Algorithm for Defining the Shortest Distance among ZigBee-Based Communication Devices in Microgrids - Setiawan, M.; Shahnia, Farhad; Ghosh, Arindam; Rajakaruna, Sumedha (Institute of Electrical and Electronics Engineers (IEEE), 2014)
To improve the controllability within Future microgrids, a communication network needs to be available to provide data transfer within the MG. Wireless technologies such as ZigBee seem to be a good alternative for data transfer within MGs mainly due to low cost, more flexibility and acceptable data transfer rate. In such networks ZigBee-based repeaters are required to strengthen the communication signals if the DG units are scattered over a vast area. This paper mainly discusses on the algorithms required for defining the shortest distance between the DG units and the MG central controller. Different methods are discussed and a new algorithm is presented. Through the numerical analyses, it is demonstrated that the proposed method leads to a high reduction in the number of repeaters than other conventional algorithms.